2010
DOI: 10.1007/s00125-010-1731-y
|View full text |Cite
|
Sign up to set email alerts
|

External validation and optimisation of a model for predicting foot ulcers in patients with diabetes

Abstract: Aims/hypothesis In 2006 a risk stratification model was developed by Boyko et al. to predict foot ulceration in patients with diabetes, using seven commonly available clinical variables. We sought to validate and optimise this clinical prediction rule in a different setting. Methods A retrospective cohort study was conducted on all patients with diabetes attending the podiatry section of a diabetic foot clinic at a tertiary hospital in Portugal (n=360). Assessment at baseline included variables evaluated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
84
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(87 citation statements)
references
References 23 publications
3
84
0
Order By: Relevance
“…In univariate analysis, six of the seven variables included in the Boyko model were also significantly associated with foot ulcer development in the external validation study [25]. Tinea pedis, as in the Boyko et al study [24], showed a statistically significant association only in multivariate analysis [25].…”
Section: Foot Ulcer Risk Stratification Systems: Data Synthesismentioning
confidence: 67%
See 4 more Smart Citations
“…In univariate analysis, six of the seven variables included in the Boyko model were also significantly associated with foot ulcer development in the external validation study [25]. Tinea pedis, as in the Boyko et al study [24], showed a statistically significant association only in multivariate analysis [25].…”
Section: Foot Ulcer Risk Stratification Systems: Data Synthesismentioning
confidence: 67%
“…It was only possible to analyse or calculate diagnostic accuracy measures (sensitivity, specificity, predictive values) in three studies [18,21,25] (Table 4). In the studies where diagnostic accuracy measures or crude data were not displayed, they were calculated by or requested from the authors [18,20,24], respectively.…”
Section: Foot Ulcer Risk Stratification Systems Identifiedmentioning
confidence: 99%
See 3 more Smart Citations